Charge-transfer states in photosynthesis and organic solar cells - Hustings, Jeroen; Bonné, Robin; Cornelissen, Rob; Morini, Filippo; Valcke, Roland; Vandewal, Koen; Manca, Jean V. (Frontiers in Photonics, 2022)
Light-induced charge-transfer mechanisms are at the heart of both photosynthesis and photovoltaics. The underlying photophysical mechanisms occurring within photosynthesis and organic photovoltaics in particular show striking similarities. However, they are studied by distinct research communities, often using different terminology. This contribution aims to provide an introductory review and comparison of the light-induced charge-transfer mechanisms occurring in natural photosynthesis and synthetic organic photovoltaics, with a particular focus on the role of so-called charge-transfer complexes characterized by an excited state in which there is charge-transfer from an electron-donating to an electron-accepting molecular entity. From light absorption to fully separated charges, it is important to understand how a charge-transfer complex is excited, forming a charge-transfer state, which can decay to the ground state or provide free charge carries in the case of photovoltaics, or radicals for photochemistry in photosynthetic complexes. Our motivation originates from an ambiguity in the interpretation of charge-transfer states. This review attempts to standardize terminology between both research fields with the general aim of initiating a cross-fertilization between the insights and methodologies of these two worlds regarding the role of charge-transfer complexes, inspiring the cross-disciplinary development of next-generation solar cells. Likewise, we hope to encourage photosynthesis researchers to collaborate with the photovoltaics field, thereby gaining further knowledge of the charge-transfer process in natural light-harvesting systems.